Transcriptional Analysis of Three Major Putative Phosphatidylinositol Kinase Genes in a Parasitic Protozoan, Giardia lamblia - Hernandez, Yunuen (2007)
The current investigation evaluates the expression of phosphatidylinositol kinase (PIK) genes in the parasitic protozoan, Giardia lamblia. The G. lamblia Genome Database revealed the presence of two putative phosphatidylinositol-3-kinase (gPI3K) and one phosphatidylinositol-4-kinase (gPI4K) genes resembling the catalytic subunit of eukaryotic PIKs. Primers, designed to amplify mRNA of these three genes, were used to measure transcription by quantitative reverse-transcriptase polymerase chain reactions. Results suggest that all three PIK genes are expressed in non-encysting and encysting trophozoites. The relative levels of the mRNA were highest in parasites cultured in pre-encysting medium that contained no bile. Two inhibitors of PIK, LY 294002 and wortmannin were found to inhibit the growth of the trophozoite in culture. However, wortmannin was more effective than LY294002. Altogether, the present study indicates that Giardia is capable of expressing PIKs that are necessary for the growth and differentiation of this pathogen.